2022
DOI: 10.1021/acs.macromol.1c02388
|View full text |Cite
|
Sign up to set email alerts
|

Size and Dynamics of a Tracer Ring Polymer Embedded in a Linear Polymer Chain Melt Matrix

Abstract: Using dynamic Monte Carlo simulations based on the bond-fluctuation model, we systematically investigate the static and dynamic properties of a tracer ring polymer in a melt composed of linear polymers. Our results reveal that the mean-square radius of gyration of a cyclic polymer is independent of the topological constraints between the ring and linear chains. The scaling exponent (ν) of the radius of gyration R g ∼ N R ν, where N R is the ring chain length, increases from 0.5 to 0.6 as the length of the line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…However, the simulation only considered symmetric blends RxLx, and thus, the behavior of asymmetric blends may differ from the symmetric case. Based on their MC simulations that are in agreement with our results, Mo et al observed that only for short matrices, a significant dependence of ring swelling on the host length occurs . As for the Mavrantzas results, the number of threadings is high.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the simulation only considered symmetric blends RxLx, and thus, the behavior of asymmetric blends may differ from the symmetric case. Based on their MC simulations that are in agreement with our results, Mo et al observed that only for short matrices, a significant dependence of ring swelling on the host length occurs . As for the Mavrantzas results, the number of threadings is high.…”
Section: Discussionsupporting
confidence: 91%
“…Aside from the MD simulations, Monte-Carlo simulations are also reported . They also found large numbers of threadings, agreeing with Mavrantzas’ atomistic MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,20 Thus, the constraint release mechanism of rings is much slower than theoretically expected. Moreover, since these penetrations lead to slow ring polymer dynamics, 21,22 the rheological properties of ring/linear blends differ from those of both the pure ring and linear melts. Specifically, a small number of linear chains drastically increases the viscosity of the ring melts, 23,24 whereas a low ring volume fraction increases the viscosity of the linear melt up to the overlapping concentration of the rings.…”
Section: Introductionmentioning
confidence: 99%
“…Rings are penetrated and interlocked by the surrounding rings, while in linear chain contaminants they are penetrated by linear chains. , Thus, the constraint release mechanism of rings is much slower than theoretically expected. Moreover, since these penetrations lead to slow ring polymer dynamics, , the rheological properties of ring/linear blends differ from those of both the pure ring and linear melts. Specifically, a small number of linear chains drastically increases the viscosity of the ring melts, , whereas a low ring volume fraction increases the viscosity of the linear melt up to the overlapping concentration of the rings .…”
Section: Introductionmentioning
confidence: 99%